Free movement in the European Union: national institutions vs common policies? - Ruhs, M (Wiley, 2017)
The current rules for “free movement” in the European Union (EU) facilitate unrestricted intra‐EU labour mobility and equal access to national welfare states for EU workers. The sustainability of this policy has recently been threatened by divisive debates between EU countries about the need to restrict welfare benefits for EU workers. This article develops a theory for why the current free movement rules might present particular challenges for certain EU member states. It focuses on the potential roles of three types of national institutions and social norms in determining national policy positions on free movement in the EU15 states: labour markets (especially their “flexibility”); welfare states (especially their “contributory basis”); and citizenship norms (focusing on the “European‐ness” of national identities). I show that these institutions and norms vary across member states and explain why we can expect these differences to contribute to divergent national policy preferences for reforming free movement.